Efek Sosiologis Keberadaan Pondok Pesantren Lirboyo Terhadap Masyarakat Kelurahan Lirboyo: Analisis Perspektif Teori Tipologi Masyarakat Dari Clifford Geertz - Khairul Mufid (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2019)
Islamic boarding school is an educational institution that is loaded with social transformation. Islamic boarding schools in Indonesia which are the oldest educational institutions are very many, including PP. Lirboyo. When talking about PP Lirboyo, then at least it can have a sociological effect on the surrounding community, in this case, the residents of Lirboyo Village. This research is rooted in the writer's intellectual humour in terms of the extent of PP. Lirboyo in transforming the surrounding community. Lest PP. Lirboyo has no impact on the local residents. By using this type of qualitative research through the Descriptive-Qualitative approach, the researcher aims to identify a problem raised in the study, as well as produce descriptive data in the form of words, oral or written about the discussion about how the sociological effect felt by the Lirboyo Village community in the presence of PP Lirboyo and how to Analyze the Theory of Typology of Communities from Clifford Geertz on the people of Lirboyo Village, Mojoroto District, Kediri City. Clifford Geertz's theory focuses on the discussion of the division of Javanese society which is divided into three typologies. Namely Abangan, Santri and Priyai. With this theory, if you can read the Lirboyo Village community through Clifford Geertz's view.